Policy Learning in The Implementation of The One Map Policy Period of 2016-2024 - Dinda Shafira Dwi Arlan; Teguh Kurniawan (Journal of Governance and Accountability Studies, 2026)
Purpose: This study analyzes the implementation of the One Map Policy (OMP) in Indonesia between 2016 and 2024 from the perspective of policy learning theory. This study aims to identify how learning from past experiences, evaluations, and interactions between actors influences changes in OMP regulations and governance from 2016 to 2024. Methodology: This study used a qualitative descriptive method with a document review. Data were collected from laws and regulations related to the OMP, government reports, academic writings and official institutional publications. The data were analyzed descriptively using Howlett’s policy learning framework to map the dynamics of policy change. Results: The study finds that OMP implementation embodies three distinct, interconnected dimensions of policy learning: technical, socio-political, and institutional. These learning processes have led to regulatory revisions (from Presidential Regulation No. 9/2016 to No. 23/2021), enhanced cross-agency coordination, and strengthened national spatial data infrastructure and transparency. Conclusions: The findings demonstrate that the One Map Policy is not merely a technocratic project but also a dynamic policy learning process. This multidimensional learning strengthens national spatial data governance, promotes inclusivity and transparency, and provides valuable lessons for policy learning in developing countries. Limitations: The study’s reliance on secondary sources and a single theoretical framework may constrain the scope of perspectives and broader applicability of its findings. Contributions: This study enriches the literature on policy learning with evidence from Indonesia and provides lessons for strengthening inclusive, data-driven, and sustainable spatial governance.